2021
DOI: 10.2147/jpr.s290852
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dorsal Root Ganglion Pulsed Radiofrequency Combined with Paravertebral Injection of Recombinant Human Interferon-α2b in Herpetic Neuralgia

Abstract: Objective The purpose of this study was to investigate the clinical efficacy of dorsal root ganglion (DRG) pulsed radiofrequency combined with paravertebral injection of recombinant human interferon-α2b in the treatment of patients with acute herpes zoster neuralgia and its preventive effectiveness on postherpetic neuralgia (PHN). Methods A retrospective analysis of 62 patients with acute herpes zoster neuralgia was implemented. All patients were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…A high IL-6 level is the main factor that leads to nerve injury and chronic pain development and may have a pivotal role in neuropathic pain development [23]. Our previous research results also revealed that in PHN patients, Gal-3 and IL-6 plasma levels were considerably higher than in normal people [12]. It can be used as an early diagnosis and a predictor of PHN [24].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A high IL-6 level is the main factor that leads to nerve injury and chronic pain development and may have a pivotal role in neuropathic pain development [23]. Our previous research results also revealed that in PHN patients, Gal-3 and IL-6 plasma levels were considerably higher than in normal people [12]. It can be used as an early diagnosis and a predictor of PHN [24].…”
Section: Discussionmentioning
confidence: 71%
“…e puncture site for CT placement was determined to be the ventral intervertebral foramen's upper edge, and the puncture pathway was developed. 1.0% lidocaine hydrochloride was used for local infiltrating anesthesia with a slow push of radiofrequency puncture (the parameters refer to our previous research [12]) under CT. Finally, the tip of the needle was located in the epigastric abdomen on the ventral side of the intervertebral foramen, and pain at the root from the site of the puncture to the chest wall may occur.…”
Section: Prf Erapeutic Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 15 showed that high‐voltage pulsed radiofrequency can relieve pain, improve sleep quality, reduce the doses of anticonvulsants and analgesics, and decrease the incidence of clinically meaningful PHN. Fei et al 22 confirmed that PRF combined with paravertebral injection of recombinant human interferon‐α2b was an effective treatment for acute stage herpes zoster neuralgia. Zhang et al 23 reported that PRF combined with intravenous lidocaine infusion can effectively relieve pain, reduce the number of analgesic drugs used, and improve sleep and quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…DRG-pulsed radiofrequency treatment can improve the state of the issuance of nerve cells and the conduction of ions in the nerve sheath membrane, producing long-term inhibition of neuronal potential issuance, thus achieving long-term pain control [ 24 ]. Pulsed radiofrequency treatment is one of the much less invasive, more stable, and safer than any other surgical procedure, thus making it one of the common treatments used by clinicians [ 25 ].…”
Section: Discussionmentioning
confidence: 99%